#itwasboundtohappen. Reflections on the specialism of book conservation in Australia during the Covid-19 Pandemic. Issue 1 (2nd January 2022) - Fitzmaurice, Camielle; O'Connor, Freya
Abstract : The Covid-19 pandemic has changed the way we work, communicate, and transmit knowledge. Conservators, who work primarily with their hands, have had time to reflect on treatment practice, dissemination of information and siloing of knowledge in the Australian book conservation context. This paper presents a preliminary environmental survey examining the ways the conservation profession has adapted and developed our practices while working, learning, and networking from home. Case studies demonstrate that there is an increased appetite for learning and knowledge/skill sharing within the book conservation community where formal qualifications, reference material, and hands-on training are limited. Current avenues of book conservation training in Australia are assessed, and the risks to knowledge loss as a generation of bookbinders and conservators retire are considered. Through this exploration, the authors posit the need for a centralised hub for the book conservation specialism as a method of capturing published online content, using technology proactively to our advantage. This paper will address the questions of successful knowledge transmission during and post-Pandemic, the benefits and disadvantages of online learning, what we can do better and how isolation has enhanced communication and collaboration in a world where we are better connected, but further apart, than ever before.